The Habit Alimentaires Analysis (Food Habit) of Hypoatherina sp. Larvae in East Pelawangan Segara Anakan Cilacap - Subiyanto Subiyanto; Herimawan M.F.; Siti Rudiyanti (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2008)
Observations about kind of food in the Hypoatherina sp. side arrested in East Pelawangan Segara Anakan Cilacap. Food habits of observation methods conducted by the method according to the number of Effendie, (1997) 6). Based on the analysis of Hypoatherina sp. larvae food habits and analysis of plankton found in the study  showed  that the  stomach contents  of  larval  size  3,1-5,0  mm or at the beginning of taking food from other species in common with the abundant natural food in the waters, where the largest constituent Bacillariophyceae class. Along with its growth, there is a change in food habits 5,1-7,0 mm long dominated by the food standards Bacillariophyceae (27.5%) and Ciliophora (24.4%).  7,1-9,0  mm long  while  the  standard  changed  to  Bacillariophyceae  (19.4%)  and  Copepod (25.9%). 9,1-11,0 mm, and in turn again to the Copepod (39%) and Cyanophyta (34%). From this research can be concluded that the Hypoatherina sp. is a type of plankton-eating fish, both types of phyto and zooplankton.   Key words : Food habit, Fish larvae, Plankton